Dexmedetomidine elevates the lethal dose threshold of bupivacaine in rats: A dosing study. (March 2020) - Pan, L; Zhang, Y; He, Y; Chen, Z; Wang, S; Xia, Y; Papadimos, TJ; Lin, W; Xu, X
Dexmedetomidine (DMED), an alpha-2 adrenoreceptor agonist, has been widely used in regional anesthesia procedures. However, the effect of DMED on local anesthetic cardiotoxicity has not been well delineated. This study consisted of two experiments. In experiment A, 42 Sprague–Dawley (SD) rats were randomly divided into 6 groups ( n = 7), each group was pretreated with DMED 0 μg kg −1 (D0 group), 1 μg kg −1 (D1 group), 3 μg kg −1 (D3 group), 6 μg kg −1 (D6 group), 12 μg kg −1 (D12 group), and 24 μg kg −1 (D24 group), administered through the right femoral vein. In experiment B, 20 SD rats were randomly divided into 4 groups ( n = 5), such as control group, DMED group, yohimbine (YOH) group, and DMED + YOH group. Each subgroup in experiment B was also pretreated similarly as in experiment A. After pretreatment of rats as described above (in experiments A and B), bupivacaine 2.5 mg kg −1 min −1 was infused to induce cardiac arrest. In experiment A, the lethal dose threshold of bupivacaine and plasma bupivacaine concentration in D3 and D6 group were higher than the other groups. In experiment B, there was no interaction between DMED and YOH in lethal dose threshold, arrhythmia time, plasma concentration of bupivacaine, and myocardial content of bupivacaine. DMED doses of 3–6 μg kg −1 elevated the lethal dose threshold of bupivacaine without involvement of the alpha-2 adrenoceptors.